Dispersion of ultrasonic surface waves in a steel–epoxy–concrete bonding layered medium based on analytical, experimental, and numerical study - Shen, Yang; Hirose, Sohichi; Yamaguchi, Yuya (Case studies in nondestructive testing and evaluation, 2014)
The epoxy-bonded steel plate strengthening method has been widely applied in retrofitting reinforced concrete structures. However, using epoxy as the adhesive will bring deterioration due to its aging and delamination. Ultrasonic Nondestructive Evaluation (NDE) is an advantaged approach to detect the delamination or the bonding quality of the layered medium. The elastic property of the adhesive material can also be estimated properly by obtaining the phase velocity of surface wave through NDE test. This research proposes an approach to estimate the elastic property of epoxy layer in a steel–epoxy–concrete bonding layered medium. By solving dispersion equations, the analytical dispersion curves are plotted. Then the influence factors to the modes and shapes of those dispersion curves are discussed. An ultrasonic NDE test on a specimen is conducted, by which the relation between phase velocity and frequency is obtained. Through inversion process, the elastic property of epoxy layer is estimated. Based on the estimated elastic constants, a numerical study of steel–epoxy–concrete layered medium is also conducted using Explicit Finite Element Method, from which the numerical dispersion curves are obtained. Through analytical, experimental, and numerical studies, the dispersion property of surface waves in the layered medium is well understood.